PERANAN ADVOKAT DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Mardiana Mardiana (SOL JUSTICIA, 2018)
The research entitled The Role of Advocates in the Criminal Justice System in Indonesia aims to know and analyze the Status and Role of Advocates in the Criminal Justice System. To find this out, this research was conducted by Palembang Police and District Court of I-A Palembang. to obtain primary data and secondary data directly related to the writing of this thesis. The data collection techniques are data obtained from field studies and direct interviews with the police, Palembang Police Investigator and District Court Judge I-A Palembang is the party responsible and directly related in handling cases of child crime and library research. Data analysis was done by using qualitative descriptive analysis. Based on the research it is found that the Role of Advocate in the Criminal Justice System in Indonesia The role of advocate in the judicial system in Indonesia is recognized as law enforcement parallel to other law enforcement profession, such as Police, Prosecutor and Judge as stipulated in Law no. 18 year 2003 about Advocate, so that with equal position is expected to advocate to enforce law professionally based on justice and truth. The duties, obligations, attitudes and responsibilities of an advocate as law enforcement are all contained in the code of ethics of the advocate profession which is used as the basis for conducting its activities. The fundamental of the duties and responsibilities of advocates is to relate between representing clients, upholding justice, honesty and human rights, and assisting judges in the process of upholding truth and justice. The responsibility of lawyers in law enforcement to God Almighty, to the Code of Advocate Ethics, To the rules of legislation and last to the public.